Entrapped in cage (EiC) scaffolds of 3D-printed polycaprolactone and porous silk fibroin for meniscus tissue engineering - Cengiz, I. F. (2020)
The meniscus has critical functions in the knee joint kinematics and homeostasis. Injuries of the meniscus are frequent, and the lack of a functional meniscus between the femur and tibial plateau can cause articular cartilage degeneration leading to osteoarthritis development and progression. Regeneration of meniscus tissue has outstanding challenges to be addressed. In the current study, novel Entrapped in Cage (EiC) scaffolds of 3D-printed polycaprolactone (PCL) and porous silk fibroin were proposed for meniscus tissue engineering. As confirmed by micro-structural analysis the entrapment of silk fibroin was successful, and all scaffolds had excellent interconnectivity (â ¥ 99%). The EiC scaffolds had more favorable microstructure compared with the PCL cage scaffolds by improving the pore size while keeping the interconnectivity almost the same. When compared with the PCL cage, the entrapment of porous silk fibroin into the PCL cage decreased the high compressive modulus in a favorable matter in the wet state thanks to the silk fibroinâ s high swelling properties. The in vitro studies with human stem cells or meniscocytes seeded constructs, demonstrated that the EiC scaffolds had superior cell adhesion, metabolic activity, and proliferation compared to the PCL cage scaffolds. Upon subcutaneous implantation of scaffolds in nude mice, all groups were free of adverse incidents, and mildly invaded by inflammatory cells with neovascularization, while the EiC scaffolds showed better tissue infiltration. The results of this work indicated that the EiC scaffolds of PCL and silk fibroin are favorable for meniscus tissue engineering, and the findings are encouraging for further studies using a larger animal model.